IL-17A-producing γδ T cells and classical monocytes are associated with a rapid alloimmune response following vascularized composite allotransplantation in mice - Tajima, Tetsuya; Zhang, Wenming; Han, Shuling; Reitsma, Andrea; Harden, James T.; Fuentes, Samuel; Sonehara, Ayaka; Esquivel, Carlos O.; Martinez, Olivia M.; Krams, Sheri M. (Frontiers in Immunology, 2025)
BackgroundVascularized Composite Allotransplantation (VCA) is an important therapeutic option for patients that incur debilitating injuries to the face or limbs. The complexity and immunogenicity of tissue types within VCA grafts pose unique challenges and necessitate the use of intensive immunosuppression; however, graft rejection remains a challenge in VCA.MethodsDeep proteomic profiling and high dimensional analysis with cytometry time of flight were used to define the cell types and effector mechanisms elicited by VCA in BALB/c (H-2Kd) > C57BL/6 (H-2Kb) limb recipients. Spleen and cervical draining lymph nodes were collected post-transplant days 1, 3, 5, and 7 (n =4–6 mice/group/day). We identified dynamic, coordinated signatures in T cell and monocyte populations associated with VCA allograft rejection.ResultsIn comparison to syngeneic transplant recipients, allogeneic recipients exhibited significant alterations in the immune cell populations within secondary lymphoid tissues. These changes included very early expansion of double-negative TCRβ- T cells, including IL-17A-producing γδ T cells, and patrolling monocytes. Subsequently, CD8+CD62L+ T cells and CD8+ effector/effector memory T cells (Teff/Tem), Ly6ChiCCR2hiCX3CR1low classical monocytes, CD4+ Teff/Tem, and CD8+CD25hiCCR7low Teff/Tem were increased by day 5. CD8+CD25hiCCR7low Teff/Tem with the highest expression of IFN-γ, perforin, and granzyme B were enriched by day 7.ConclusionsHigh dimensional proteomic analysis reveals multiple innate and Teff/Tem subsets in acute rejection following VCA. In particular, IL-17A-producing γδ T cells and classical monocytes may be particularly important in initiating the alloimmune response in VCA recipients.